Comparison of methods of trial for detection of bacteriuria in samples from the Maringá district and the University Hospital of Santa Maria - Horner, Rosmari (2009)
The urinary tract infections are the most common infectious diseases in clinical practice and, they are also the most frequent at the hospital setting. The objective of this article was to compare the methods: 2,3,5-trifeniltetrazólio (CTT), GRAM staining, and physical-chemical tests, as a screening for urine culture. Sixty-nine samples of urine from the Maringá district, Santa Maria-RS collected from February to July 2007were analyzed. All of them had the medical request for urine culture. For the purpose of comparison, 104 samples collected in the hospital from May to July were sent to the microbiology sector of the HUSM. Ten (14.5%) out of the 69 community samples showed positive results in the culture, while 17 (16.36%) from the 104 hospitals samples were positive. The CTT was positive in 5 (50%) of 10 positive samples of the community, and 8 (47.1%) of the hospital samples. From the results obtained we concluded that the method of GRAM staining is more effective, when compared with the evidence of nitrite and leukocytes; once it presents better agreement with the urine culture and the lowest level of interference.